Echinoderms (Echinodermata) from the Central Mexican Pacific - Granja-Fernández, Rebeca (2021)
Introduction: The echinoderms from the Central Mexican Pacific are of high scientific interest and, prior to this present work, there was a lack of basic information that included incomplete checklists with inconsistencies in systematics and spatial distribution. Objective: To provide a historical review, and an updated checklist with a more complete richness of echinoderms for each state and island of the region. Methods: A checklist was elaborated based on an exhaustive literature search of the Echinodermata, and was complemented with taxonomical revisions of Ophiuroidea scientific collections. All the geographical coordinates of the records were validated. Results: The region harbors 187 species of Echinodermata: three Crinoidea, 35 Asteroidea, 67 Ophiuroidea, 32 Echinoidea, and 50 Holothuroidea. We detected 52 records in the literature that must be considered as invalid and five as doubtful. We provide 16 new records of Ophiuroidea from different states and islands; of them, four are new records for the region. Jalisco presented the highest number of species (84), followed by the coast of Nayarit (74), Michoacán (63), and Colima (55); among the islands, Revillagigedo showed the major number of species (85) followed by Marías (81), Marietas (48), and Isabel (44). Conclusions: The numbers of species known in the region are mostly related to both sampling effort and environmental characteristics that promote high biodiversity. The Central Mexican Pacific is an oceanographic region with mixed conditions from the North and South of the Mexican Pacific, and therefore, with a biogeographical importance reflected in its species richness.